2019
DOI: 10.1016/j.ekir.2019.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Complement Factor H–Related Protein 5 (FHR5) Is Highly Prevalent in C3 Glomerulopathy and Associated With Renal Impairment

Abstract: Introduction: Therapeutic agents that target complement are increasingly available for glomerular diseases. However, the mechanisms linking glomerular complement deposition with inflammation and damage are incompletely understood. Complement factor H-related protein 5 (FHR5) interacts with complement C3 and is considered to promote activation. Circulating and glomerular FHR5 associates with IgA nephropathy and abnormal FHR5 associates with familial C3 glomerulopathy (C3G). We characterized glomerular FHR5 stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…Interestingly, the authors found a similar array of complement proteins as described by mass spectrometry, with comparable results in C3GN and DDD. A novel finding was the high prevalence of FHR5 in C3G glomeruli, where the intensity of staining correlated positively with the presence of a membranoproliferative pattern and with the staining intensities of C3 activation products (C3b/iC3b/C3c and C3dg) and C5b-9, and correlated negatively with estimated glomerular filtration rate at biopsy 5 . These results suggest potential mechanistic relevance.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…Interestingly, the authors found a similar array of complement proteins as described by mass spectrometry, with comparable results in C3GN and DDD. A novel finding was the high prevalence of FHR5 in C3G glomeruli, where the intensity of staining correlated positively with the presence of a membranoproliferative pattern and with the staining intensities of C3 activation products (C3b/iC3b/C3c and C3dg) and C5b-9, and correlated negatively with estimated glomerular filtration rate at biopsy 5 . These results suggest potential mechanistic relevance.…”
mentioning
confidence: 78%
“…In this issue, Medjeral-Thomas et al. 5 applied a large battery of antibodies to individual complement factors and their regulatory proteins (including FHR5, FHR1, fH, C3b/iC3b/C3c, C3dg, C5b9, C1q, C4d, and properdin) to formalin-fixed paraffin-embedded (FFPE) biopsy samples from 19 patients with C3G (including 13 with C3GN and 6 with DDD). They catalogued the spectrum of immunohistochemistry results and made correlations with clinical and outcome parameters.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We speculate that glomerular FHR proteins are only likely to clear from glomeruli when C3d has been removed. In this context, it is notable that in human C3G, factor H-related protein 5 associates with glomerular C3d 29 .…”
Section: Igg-fh 1-5 Ameliorated Renal Injury During Antn In Cfh -/Micementioning
confidence: 99%